Categorization of augmented reality and geolocation applications for mobile learning - Fombona, Javier; Vázquez-Cano, Esteban; Del Valle Mejias de Villalba, María Elena (Perspectiva Educacional, 2017)
This educational research focuses on describing the potential of the advanced digital mobile devices, especially the Augmented Reality, AR, and Geolocation techniques. A number of 231 students experienced and recorded the characteristics of 231 apps to group them into several categories. We, then, turn to describe the potential of AR to create engaging e-learning experiences in field activities. Similarly, Geolocation and Global Positioning System, GPS technology, allow the interaction between the users and their geographical situation. It also enables them to download information about the place, or other activity associated with a spot. These ICT resources motivate students and generate a challenge for developing classical tasks in a more dynamic and collaborative way. within the traditional educational framework. For the first time, static places and specific moments to access information disappear. M-learning modifies teaching methods since the spatial reference of the classroom changes through a physical and virtual context dominated by the user, with an absent teacher.